Pengembangan Potensi Lokal Ikan Tuna Sirip Kuning (Thunnus albacares) Menjadi Cemilan Sehat untuk Mencegah Stunting di Kota Sorong, Papua Barat Daya - Saif, Sulfiana; Hardianti, Fatimah; Muslimin, Istyqamah; Marselina Ghela, Maria; Kelibay, Amirula; Tanasali, Fadalia (Jurnal Galung Tropika, 2024)
Based on the results of the Indonesian Nutrition Status Survey (INSS), the prevalence of stunting in West Papua was recorded at 26,02% in the previous year, increasing to 30.00% in 2022. Currently, most children pay less attention to the food type and more often consume unhealthy snacks. This research aims to develop the product of yellowfin tuna fish sticks to meet the nutritional balance of children and prevent stunting. The treatment in this research was adding yellowfin tuna sih meal with the formulation of wheat flour, tapioca flour, and fish flour, namely 100 g: 100 g: 75 g, which was used in making stick products. Testing of yellowfin tuna fish sticks includes hedonic and nutritional content tests. Based on the results of the hedonic test, which includes the parameters of appearance, smell, taste, and texture, yellowfin tuna fish sticks obtained a score that meets SNI standards, namely 7 (seven) for each criterion. Testing the nutritional content shows that yellowfin tuna sih sticks have a water content of 5,11%, protein of 24,11%, fat of 26,28%, fiber of 0,65%, ash of 3,91%, and carbohydrates of 39,91%, according to product specifications.